Optimization of the Duration of Ultrasonic Shot Peening for Enhancement of Fatigue Life of the Alloy Ti-6Al-4V - Kumar S.; Chattopadhyay K.; Singh V. (My University, 2025)
In the present investigation, surface nanostructure was developed on the alloy Ti-6Al-4V using ultrasonic shot peening (USP) and its effect was studied on tensile strength and low-cycle fatigue (LCF) behavior. The gage section of tensile and LCF samples was ultrasonic-shot-peened (USPed) for durations of 2.5, 5.0 and 7.5 min with hard steel shots of 3 mm diameter at constant frequency of 20 kHz using StressVoyager to modify the surface. The yield and tensile strength increased; however, ductility was marginally reduced due to USP. Some of the ultrasonic-shot-peened samples were stress-relieved (SR) at 400 °C for 1 h. LCF tests were conducted on the non-ultrasonic-shot-peened (non-USPed), USPed and USPed + SR samples at different total strain amplitudes (± Δεt/2) of 0.95, 0.85, 0.75 and 0.65% at constant strain rate of 1 × 10−3 s−1. LCF life of the USPed samples was found to be higher than that of the non-USPed sample. LCF life of the USPed specimen at Δεt/2 = ± 0.65% was enhanced by ~ 4 times that of the non-USPed sample. However, the enhanced LCF life of the USPed samples was reduced following stress relieving treatment at 400 °C due to relaxation of the associated compressive stress, though it was still higher than that of the non-USPed sample. © 2020, ASM International.